Using Different Methods to Tenderize Spent Hens Meat - Al-Hajo, N.A. Nadia (International Journal of Poultry Science, 2008)
The aim of this study is tenderizing spent hens meat by using cheap local materials such as bitter orange juice, vinegar, salt and sugar for 1,2, 3 and 4h, distill water is used (T1) in curing to make it as standard. Bitter orange juice (acidity of 1.5) (T2), vinegar (acidity of 7) (T3), table salt (2%) (T4) and sugar (2%) (T5) were used. The processed meat was storied under -18oC ± 2oC for a month to investigate the influence of the type of treatment and the periods of storing and submersion on the sensory properties and chemical qualities through estimating the percentage of moisture, hydrogen number pH, volume of the released extract. A sensory properties evaluation of the qualities of flavor, juiciness, tenderness and overall acceptance was carried out. Results of curing in the different solutions revealed a decreased pH value in (T2) and T3 ; while the highest significant differences (p<0.05) was in samples T4. Besides, there were no significant differences concerning the periods of curing. As far as the period of freezing is concerned, a significant increase in pH of the samples was noticed, T4 had the upper degree. There were no significant differences concerning the periods of curing. The percentage of moisture increased significantly (p<0.05) of the treatment groups compared with T1. The highest significant differences (p<0.05) were found in T4. A significant (p<0.05) increase occurred in the percentage of moisture when it was frozen and cured. Besides, there were significant differences (p<0.05) concerning the period of curing. A decrease was noticed of the volume of the released extract. The highest significant (p<0.05) difference was in T1 and the lowest one was in T4. It was also noticed that significant (p<0.05) increase of the frozen sample, the highest significant difference (p<0.05) was in T1 and the lowest one was in T4. Results of sensory evaluation indicated the improvement of the sensory qualities of the samples treated with the different solutions especially of tenderness and juiciness. These results were reflected on the quality of general acceptance by the consumer of the samples. Results of sensory evaluation revealed that T2 and T4 was the best sample. Significant differences (p<0.05) as far as the periods of curing were noticed. Thus we can recommend using 2% salt and bitter orange juice (1.5 acidity) in curing spent hens meat.